紫苏籽油的抗衰老作用及机制探究 Anti-aging effect and mechanisms of perilla seed oil - 王荣1,2,3，王娜娜1,2,3，杨宽1,2,3，刘自群1，秦蓓1,2,3 WANG Rong1,2,3，WANG Nana1,2,3， YANG Kuan1,2,3， LIU Ziqun1，QIN Bei1,2,3 (Zhongguo youzhi)
旨在为紫苏籽油的开发利用提供理论依据，以D-半乳糖（500 mg/kg）在小鼠颈背部皮下连续注射4周建立小鼠衰老模型后，将小鼠随机分为模型对照组（生理盐水）、阳性对照组（维生素C 200 mg/kg）和紫苏籽油高（5 mL/kg）、中（2.5 mL/kg）、低（1.25 mL/kg）剂量组，连续灌胃4周，记录小鼠体质量及行为变化，通过转棒法和金属网法检测小鼠的协调运动能力，测定小鼠主要脏器（脑、胸腺、脾脏）指数以及小鼠血清和脑组织匀浆中谷胱甘肽过氧化物酶（GSH-Px）活力和丙二醛（MDA）含量，并通过苏木精-伊红（HE）染色观察小鼠脑组织病理形态。结果表明：与模型对照组比较，紫苏籽油高、中剂量组小鼠的在棒时间和在网时间显著延长 (p<0.05)，增强了小鼠的运动能力；紫苏籽油各剂量组小鼠脑指数均显著增加（p＜0.05），其中低剂量组小鼠的脾脏指数也显著增加（p＜0.05）；紫苏籽油高、中剂量组小鼠血清中GSH-Px活力显著增加（p＜0.05），中剂量组小鼠的脑组织中MDA含量显著降低(p<0.05)；紫苏籽油各剂量组小鼠的脑组织细胞排列趋向有序，细胞结构完整。综上，紫苏籽油可通过抑制氧化应激发挥抗衰老作用。 Aiming to provide a theoretical basis for the development and utilization of perilla seed oil, the aged mice model was established by injecting D-galactose(500 mg/kg) for continuous 4 weeks at neck back. Mice were randomly divided into model control group, positive control group (VC 200 mg/kg), and perilla seed oil high (5 mL/kg), medium (2.5 mL/kg) and low (1.25 mL/kg) dose groups. After continuous administration for 4 weeks, the body weight and behavioral changes in mice were observed. The motor coordination ability of mice was evaluated by rotarod test and metal mesh method. The organ indexes of brain, thymus and spleen were calculated. The GSH-Px activity and MDA content in serum and brain tissue were evaluated. The pathological morphology in brain tissue were observed by HE staining. The results showed that compared with model control group, the high and medium dose perilla seed oil significantly prolonged the time in rod spinning and on the mesh (p<005), respectively, indicating motor coordination ability of mice was enhanced. The brain index significantly increased in all dose groups of perilla seed oil, and the spleen index also significantly increased in the low dose group. The activity of GSH-Px in serum was significantly improved in the medium and high dose perilla seed oil groups(p<005). The content of MDA in brain were significantly reduced in the medium dose perilla seed oil group (p<0.05). HE staining revealed that the cells in brain tissue of perilla seed oil groups tended to be arranged in an orderly manner, and the cellular structures were intact. In conclusion, perilla seed oil can inhibit the oxidative stress injury and play an anti-aging role in mice.